If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 = 2w + 3(w + -4) Reorder the terms: -27 = 2w + 3(-4 + w) -27 = 2w + (-4 * 3 + w * 3) -27 = 2w + (-12 + 3w) Reorder the terms: -27 = -12 + 2w + 3w Combine like terms: 2w + 3w = 5w -27 = -12 + 5w Solving -27 = -12 + 5w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-5w' to each side of the equation. -27 + -5w = -12 + 5w + -5w Combine like terms: 5w + -5w = 0 -27 + -5w = -12 + 0 -27 + -5w = -12 Add '27' to each side of the equation. -27 + 27 + -5w = -12 + 27 Combine like terms: -27 + 27 = 0 0 + -5w = -12 + 27 -5w = -12 + 27 Combine like terms: -12 + 27 = 15 -5w = 15 Divide each side by '-5'. w = -3 Simplifying w = -3
| 9+3p-5t+3= | | 31-7r=-6r-4(1-r) | | -5-2/7x=-1 | | -5-2/7x=25 | | 2(x+3)+5x=12 | | -90=5(2n-8) | | t/-6-8=7 | | 4+1/3y=-5 | | -3/2x-9=6 | | u/9=1 | | 5x/8=2x/3-1 | | 5x+13=9x-39 | | -7p+3p=8 | | 3lnx=2 | | 7z-8=3z+24 | | -2/5x-1=3 | | 777/6 | | -4(x+5)=3(x-11) | | 2x-0.3-2.6x=3.42 | | 2x*5=11 | | v+5=8 | | 8=-5/6z-12 | | 2-3(3x-4)+5=52 | | -3(x+8)-2(4x-3)=-7 | | -3=5v-5 | | Xlnx=6lnx | | x+3.5=9 | | (4f+5)-(-5f-40)=180 | | -94-x=-12x+49 | | 13x^2-16x=4 | | 4(k+5)=2(9t-2) | | 4(v-8)=-2v-26 |